Screening for chronic kidney disease in Belgrade primary health care centers - Ljubica Đukanović; Višnja Ležaić (Биомедицинска истраживања, 2018)
Introduction: Academy of Medical Science of Serbian Medical Society introduced collaboration between Belgrade nephrologists and general practitioners with the aim of examining the prevalence of chronic kidney disease (CKD) in populations at risk as well as of checking whether collaboration with general practitioners contributed to implementation of regular CKD screening. Methods: The research encompassed two studies carried out in four Belgrade Primary Health Care Centers. The screening study involved 619 patients at risk for CKD (348 with hypertension, 206 with diabetes, 65 persons aged > 60 years without hypertension/dia-betes) in whom glomerular filtration rate (eGFR) was estimated by MDRD formula, while urine dipstick test was used for detection of proteinuria and albuminuria (Micral-test® strips).The second study was retrospective analysis of medical records of 450 patients who were examined in the screening study and whose blood pressure and eGFR recording were analyzed during three-year period. Results: In screening study, eGFR below 60 ml/min/1.73m 2 was detected in 121 (19.55%) and albuminuria in 242 (39.10%) patients. During three-year retrospective study, percentage of patients whose blood pressure and eGFR were recorded decreased from 42% to 22% and from 42% to 18%, respectively. Multivariate regression analysis selected health center, systolic blood pressure and hypertension as the variables significantly associated with the number of years in which blood pressure was recorded, while male gender, health center, hypertension and basal eGFR as variables associated with the number of years in which eGFR was recorded. Conclusion: Despite collaboration between nephrologists and general practitioners in screening study, the retrospective three-year study revealed insufficient recording of blood pressure and eGFR in patients' medical records.
Keywords: chronic kidney disease; screening; primary health care